2017
DOI: 10.4103/0259-1162.206851
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine as an adjuvant for intravenous regional anesthesia in upper limb surgeries

Abstract: Background:Intravenous regional anaesthesia is a simple, safe and effective technique with good success rate for upper limb surgeries. The duration of postoperative analgesia is an important limitation of this technique. Various adjuvants have been used to overcome this drawback. In this study we evaluate the effect of dexmedetomidine 0.5 μgkg-1 as an adjuvant for lignocaine intravenous regional anaesthesia.Methods:Sixty patients scheduled to undergo upper limb surgery were randomised to receive intravenous re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In the present study a rapid onset of sensory and motor blockade as well as a longer duration of sensory and motor blockade after cuff deflation were observed with the use of dexmedetomidine as an adjuvant to lignocaine for IVRA. Subramanya et al (9) and Memis et al (10) have reported that the addition of 0.5 µg kg −1 of dexmedetomidine to lignocaine for IVRA significantly reduced the duration of the onset of sensory and motor blockade, improved the quality of anesthesia and postoperative analgesia without any side effects. Esmaoglu et al (8) examined the intraoperative effects and postoperative analgesia of dexmedetomidine when used as an adjunct for IVRA in 40 patients undergoing hand surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study a rapid onset of sensory and motor blockade as well as a longer duration of sensory and motor blockade after cuff deflation were observed with the use of dexmedetomidine as an adjuvant to lignocaine for IVRA. Subramanya et al (9) and Memis et al (10) have reported that the addition of 0.5 µg kg −1 of dexmedetomidine to lignocaine for IVRA significantly reduced the duration of the onset of sensory and motor blockade, improved the quality of anesthesia and postoperative analgesia without any side effects. Esmaoglu et al (8) examined the intraoperative effects and postoperative analgesia of dexmedetomidine when used as an adjunct for IVRA in 40 patients undergoing hand surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine is a selective α2-adrenergic agonist that can prolong and enhance the local anesthetic action by exerting a direct effect on peripheral nerve activity (7) . Studies have evaluated the use of dexmedetomidine as an adjuvant in IVRA at doses of 1 µg kg −1 and 0.5 µg kg −1 (8,9) . The present study compared the effect of the addition of 30 µg of dexmedetomidine to 2% lignocaine with 2% lignocaine alone in IVRA on intraoperative tourniquet pain, fentanyl consumption, onset and duration of sensory and motor blockade, duration of postoperative analgesia, and overall patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“… 3 4 However, its focal limitation is on the onset and swift development of pain following tourniquet deflation, most notably once operations are prolonged. 3 5 …”
Section: Introductionmentioning
confidence: 99%
“… 1 4 Because an increased peripheral nerve compression is reported to be accounted for by ischemia following tourniquet inflation, the role of a nerve fibers and non-myelin C-fibers was judged significantly contributory in causing tourniquet pain. 3 5 Varying studies were established to include drugs like morphine, meperidine, magnesium sulfate, fentanyl, sufentanil, clonidine, nitroglycerin, granisetron added to the local anesthetic solution to lengthen the analgesia duration. 5 6 Notwithstanding abundant papers on the analgesic effects of transdermal nitroglycerin, 7 evidence about the effect of intravenous nitroglycerin in IVRA is bounded to the study led by Sen et al 8 who first appraised the effect in the surgical interventions for carpal tunnel, trigger finger, and tendon release, suggesting nitroglycerin-derived pain relief benefits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation